A coluna da morte: memórias, representações e a escrita de si do tenente João Cabanas (1924-1928) - Tecchio, Caroline (2021)
Analyze the representations of João Cabanas and writing his book The Death Column guided the production of this thesis. The leader lieutenants fought in the Levant Paulista 1924 and stood by the use of audacious military strategies, especially ahead of the Death Column, a subdivision of the column Paulista that has existed since the withdrawal of the lieutenants of the city of São Paulo, by mid-1925. In 1926, he published the book during his exile in Paraguay, doing of the writing a possibility for self-defense, given the derogatory image built over it by loyalists. In addition to the book, I work with other sources, including the newspaper Correio Paulistano, the survey report published in book form, entitled Levante Subversivo of 1924, and the books Narrando a Verdade and The Rest of Truth, written by Abílio de Noronha. This study deals with the self-representations of João Cabanas and the representations about him and the Column of Death. To meet this objective, the study is inserted in the field of Cultural History, and works with the concepts of representation, memory and writing of the self.